A study on means of escape for Person With Disabilities (PWDs) in Shopping Mall with the conformity to Malaysian Standard (MS1183:1990 Code Of Practice For Means of Escape For Disabled Person) / Nurul Ili Nabihah Jamian - Jamian, Nurul Ili Nabihah (Faculty of Architecture, Planning and Surveying, 2014)
Person with disabilities (PWDs) are the people which have hearing, visual, physical, cognitive and sensory impairment. They are special people where they need attention to be given not only in terms of their facilities but also in term of their safety especially in public building. Most of attention was focused on getting into premises to enable disabled people to fully use the building, but they also needs to enable them to leave safely from the premises. The safe evacuation of disabled people is a problematic area that has not received sufficient attention to date. The purposes of this research are to study on the general requirements for means of escape for PWDs in shopping mall with comply to the Malaysian Standard (MS1183:1990). Department of Standard Malaysia have provide the Malaysians Standards (MS1183:1990 Code Of Practice For Mean Of Escape For Disabled Persons) that need to be comply by all premises in Malaysia. This guideline must be follow in order for the safety of person with disabilities in case of emergency. By holding on this current issued, this research has been done whereby the aim of this research is to provide good requirement of means of escape for PWDs in shopping mall with the conformity to the Malaysian Standard (MS1183:1990). With the finding obtained from data collection and analysis confirm that all the case study area in this research are mostly have follow the general requirement of means of escape for PWDs in the shopping malls. However, some of the requirement did not comply with Malaysians Standard (MS1183:1990). In order to achieve good requirement in the aspect of means of escape in shopping malls, the authority should conduct an inspection on shopping malls in order to overcome these problems. Further, the recommendation stated in the study also will help the management of shopping mall to implements the best strategies, in order to improve the means of escape for PWDs in the shopping malls.